A method for defining the CORE of a psychosocial intervention to guide adaptation in practice: Reciprocal imitation teaching as a case example. (April 2022) - Edmunds, Sarah R; Frost, Kyle M; Sheldrick, R Chris; Bravo, Alice; Straiton, Diondra; Pickard, Katherine; Grim, Valerie; Drahota, Amy; Kuhn, Jocelyn; Azad, Gazi; Pomales Ramos, Anamiguel; Ingersoll, Brooke; et al.
Defining the central components of an intervention is critical for balancing fidelity with flexible implementation in both research settings and community practice. Implementation scientists distinguish an intervention's essential components (thought to cause clinical change) and adaptable periphery (recommended, but not necessary). While implementing core components with fidelity may be essential for effectiveness, requiring fidelity to the adaptable periphery may stifle innovation critical for personalizing care and achieving successful community implementation. No systematic method exists for defining essential components a priori . We present the CORE (CO mponents &R ationales forE ffectiveness) Fidelity Method—a novel method for defining key components of evidence-based interventions—and apply it to a case example of reciprocal imitation teaching, a parent-implemented social communication intervention. The CORE Fidelity Method involves three steps: (1) gathering information from published and unpublished materials; (2) synthesizing information, including empirical and hypothesized causal explanations of component effectiveness; and (3) drafting a CORE model and ensuring its ongoing use in implementation efforts. Benefits of this method include: (1) ensuring alignment between intervention and fidelity materials; (2) clarifying the scope of the adaptable periphery to optimize implementation; and (3) hypothesizing—and later, empirically validating—the intervention's active ingredients and their associated mechanisms of change. Lay abstract: Interventions that support social communication include several "components, " or parts (e.g. strategies for working with children and families, targeting specific skills). Some of these components may be essential for the intervention to work, while others may be recommended or viewed as helpful but not necessary for the intervention to work. "Recommended" components are often described as "adaptable" because they can be changed to improve fit in different settings where interventions are offered or with different individuals. We need to understand which parts of an intervention are essential (and which are adaptable) when translating interventions from research to community settings, but it is challenging to do this before studying an intervention in the community. This article presents the CORE (CO mponents &R ationales forE ffectiveness) Fidelity Method—a new method for defining the essential components of evidence-based interventions—and applies it to a case example of Reciprocal Imitation Teaching, an intervention that parents are taught to deliver with their young children with social communication delays. The CORE Fidelity Method involves three steps: (1) gathering information from multiple sources; (2) integrating information from previous research and theory; and (3) drafting a CORE model for ongoing use. The benefits of using the CORE Fidelity Method may include: (1) improving consistency in intervention and research materials to help all providers emphasize the most important skills or strategies; (2) clarifying which parts of the intervention can be adapted; and (3) supporting future research that evaluates which intervention components work and how they work.